STRATEGI DALAM MENINGKATKAN OMZET PENJUALAN PADA TOKO DUO SISTER HIJAB KOTA BENGKULU - Annisa Murti; Sri Ekowati (UM. Bengkulu, 2021)
Sister Duo Hijab store is a company engaged in fashion which produces and markets hijab, clothes, pants, hijab shirts, tuspins etc. This business has been running for 3 years and is growing well but has many competitors in the same field. This study is entitled